Botulinum toxin efficacy and safety in geriatric patients with overactive bladder: Turkish first multicenter study - Karakeci, A.; Keles, A.; Onur, R. (Wiley, 2019)
[Abstract Not Available]
Keywords: overactive bladder; botulinum neurotoxin A; quality of life; geriatric patients